2021
DOI: 10.1038/s41598-021-83832-7
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil N2O emission and nitrogen utilization to organic matter in the wheat and maize rotation system

Abstract: The appropriate nitrogen (N) fertilizer regulator could increase N utilization of crops and reduce N losses in the North China Plain. We investigated the effects of reduced inorganic-N rate combined with an organic fertilizer on nitrous oxide (N2O) emissions in winter wheat and summer maize rotation system. Simultaneously studied the effect of different treatments on N use efficiency (NUE), N balance and net income. After reducing the amount of nitrogen fertilizer in the wheat-corn rotation system, the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Additionally, soil N 2 O emissions are negatively correlated with soil NO 3 – N and soil pH. This is because a large amount of precipitation enters the soil during the rainy season, which increases soil moisture and converts soil NO 3 – N to NH 4 + -N, and the soil becomes a low-oxygen environment, which provides the most suitable conditions for denitrification and greatly increases N 2 O emissions 57 . Studies have shown that pH is positively correlated with N 2 O produced by the denitrification process of nitrifying bacteria, and negatively correlated with N 2 O produced by denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, soil N 2 O emissions are negatively correlated with soil NO 3 – N and soil pH. This is because a large amount of precipitation enters the soil during the rainy season, which increases soil moisture and converts soil NO 3 – N to NH 4 + -N, and the soil becomes a low-oxygen environment, which provides the most suitable conditions for denitrification and greatly increases N 2 O emissions 57 . Studies have shown that pH is positively correlated with N 2 O produced by the denitrification process of nitrifying bacteria, and negatively correlated with N 2 O produced by denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing nitrogen fertilizer use can help control these harmful gas emissions [189]. Initially, inorganic fertilizers were promoted, but now Organic Nitrogen is recommended due to its favorable yield results and fewer harmful effects [190].…”
Section: Atmospheric Effects: Emission Of Ammonia and Nitrous Oxidementioning
confidence: 99%
“…Nitrous oxide (N 2 O) emissions have a global warming potential 298 times higher than carbon dioxide (over a 100‐year time frame), accounting for 6% of climate warming from human activities (IPCC, 2021), and also a strong stratospheric ozone depletion potential (Ravishankara et al, 2009). Agriculture is responsible for more than 80% of anthropogenic N 2 O emissions (IPCC, 2021), most of which are released from soils after the application of organic and inorganic fertilizers (Han et al, 2017; Shu et al, 2021). Although several groups of soil microorganisms can produce N 2 O emissions, nitrifiers, and denitrifiers are often considered the main source (Butterbach‐Bahl et al, 2013).…”
Section: Introductionmentioning
confidence: 99%